Silver-Catalyzed Tandem Trifluoromethylation and Cyclization of Aryl Isonitriles with the Langlois Reagent - Liu, Yu-Rong; Tu, Hai-Yong; Zhang, Xing-Guo (Synthesis, 2015)
A mild and efficient procedure for the silver-catalyzed tandem trifluoromethylation and cyclization of aryl isonitriles with the Langlois reagent (sodium triflinate) is developed. A series of trifluoromethylated phenanthridines is prepared in moderate to good yields from a cheap and stable trifluoromethyl source.
Keywords: phenanthridines; trifluoromethylation; Langlois reagentcyclization